First evidence of microplastics ingestion by freshwater fishes from Nong Luang Wetland, Chiang Rai, Thailand - Kittichai Chantima,; Krittawit Suk-Ueng,; Paridchaya Intep,; Saritporn Vittayapadung, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Microplastic (MP) ingestion has been reported in several marine species but knowledge regarding MPs in freshwater species is limited, with only a few studies on the occurrence of MPs in freshwater fish, particularly in Thai freshwater ecosystems. The aim of this study was to assess the occurrence of MPs for the first time in the gastrointestinal tracts (GITs) of freshwater fishes from the Nong Luang Wetland, Chiang Rai, Thailand. A total of 100 fish specimens representing 15 species from 8 families were examined. Basic fish measurements as total length and total weight were used to calculate Fulton’s condition index (F). The GITs were subsequently removed and MPs were extracted by visual inspection and digestion solution. Qualitative attributes such as color and MP types (fibers, rod-shaped and fragments) were also recorded. Results showed relatively low MP prevalence at 21.0%, with 25 MP particles removed from the GITs of specimens representing 7 species. The number of ingested MP particles ranged between 1 and 4 per fish, with an average of 1.19±0.68. MP particles were categorized as fibers (92.0%), rod-shaped (4.0%) and fragments (4.0%) with blue fibers the most prevalent. No significant correlations were observed between the number of MP particles and the body length, weight, and F value of fish. These findings provide the first evidence of MP contamination in fishes from a Thai wetland as a baseline for future studies and risk assessments on the biota of many aquatic systems spread across the country.